Computational screening of boswellic acid for its antibacterial activity against acne-causing bacteria via molecular docking - Dedi Damhuri; Ietje Wientarsih; Rini Madyastuti Purwono; Agustin Indrawati; Asri Rizky; Jessica Anggun Safitri; Ahmad Syarifuddin (Universitas Gadjah Mada, 2025)
Acne vulgaris (AV) is a common inflammatory-skin disorder associated with bacterial infections, particularly Cutibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. The rising resistance to conventional antibiotics has prompted the exploration of natural compounds such as boswellic acid, which is known for its antibacterial potential. This study aimed to evaluate the antibacterial activity of boswellic acid using an in-silico approach through molecular docking against several essential bacterial target proteins implicated in acne pathogenesis. The boswellic acid ligand was obtained from the PubChem database, while the three-dimensional structures of the target proteins were retrieved from the RCSB Protein Data Bank. Blind docking was performed using AutoDock Tools version 1.5.7 and AutoDock Vina, followed by interaction analysis using Discovery Studio Visualizer and Visual Molecular Dynamics (VMD). Nine bacterial proteins involved in vital cellular processes such as metabolism, protein synthesis, biofilm formation, and DNA replication were selected, including transcriptional regulator TcaR, penicillin-binding proteins (PBPs), tyrosyl-tRNA synthetase (TyrRS), 3-ketoacyl-ACP synthase III (KAS III), CRISPR-associated protein, DNA gyrase, transcriptional regulator MarR, methylmalonyl-CoA epimerase, and accumulation-associated protein (Aap). The docking results demonstrated that all target proteins exhibited negative binding energy values (< 0), indicating thermodynamically stable and spontaneous interactions. Among these, TcaR displayed the highest binding affinity with a binding energy of −10.2 kcal/mol and formed nine conventional hydrogen bonds, reflecting a particular and stable interaction. Key interacting residues included Gln: B61, HisA:42, AsnA:20, AsnB:17, and Arg1:110. In contrast, the Aap protein formed only one covalent bond, indicating the weakest interaction. These findings suggest that boswellic acid effectively inhibits key bacterial proteins, particularly those involved in transcriptional regulation and biofilm development. Therefore, boswellic acid holds significant potential as a safe and effective topical antibacterial agent for further growth in biomedical engineering-based formulations.